An assessment of micro- and nanoplastics in the biosphere: A review of detection, monitoring, and remediation technology - Patil, Swapnil M.; Rane, Niraj R.; Bankole, Paul O.; Krishnaiah, Prakash; Ahn, Yongtae; Park, Young-Kwon; Yadav, Krishna Kumar; Amin, Mahammed A.; Jeon, Byong-Hun (ELSEVIER SCIENCE SA, 2022)
Plastics have become a pervasive feature of modern life and are used in every aspect of modern-day life, from agriculture to microchips. Microplastics and nanoplastics (MNPs) have been detected in marine and terrestrial ecosystems, and even in areas distant from the source of origin. There are still questions related to the source, weathering, transportation, and ecological impacts of biospheric MNPs. The problem is caused by inadequate physical analysis and lack of methods for standardizing sampling and identifying biospheric MNPs. There are only a few review papers that emphasize the sources of MNPs and their occurrence in various organisms. Monitoring and detection of MNPs in the environment, as well as physical-chemical and biological methods for their removal, are still unclear. The mechanism underlying the formation of MNPs, factors affecting their transportation and distribution in the biosphere are reviewed here. This review provides a comprehensive summary and analysis of the latest research updates on quantification, analysis, and abatement of MNPs. The comparisons of removal technologies based on their performance, sensitivity, economic feasibility, and volume handling capacity could help to design an efficient MNPs remediation strategy considering the source, characteristics, concentration, and volume of samples. Insights for future research recommendations are provided by identifying existing research loopholes and futuristic methodologies for MNPs detection, entrapment, and removal from the biosphere.